+0  
 
0
304
3
avatar

Let f(x)=6(2)x−1+4 . 

The graph of f(x) is stretched vertically by a factor of 4 to form the graph of g(x) . 

What is the equation of g(x)

?

 

Enter your answer in the box.

g(x) = 

 Dec 12, 2017
edited by Guest  Dec 12, 2017
 #1
avatar+7352 
+2

g(x)   =   4 * f(x)

         =   4 * ( 6(2)x − 1 + 4 )

         =   4 * ( 12x + 3 )

         =   48x + 12

 Dec 12, 2017
 #2
avatar+98196 
+2

Thanks, hectictar...... !!!!

 

I think this could also be  :

 

f(x)   =  6(2)x - 1  +  4

 

4f(x)  =  g(x)

 

4 [ 6(2)x - 1  +  4 ]    =

 

24(2)x - 1  +  16  =   g(x)

 

 

 

cool cool cool

 Dec 12, 2017
 #3
avatar
+1

THANK YOU BOTH!!!!

Guest Dec 12, 2017

26 Online Users

avatar
avatar
avatar
avatar
avatar
avatar